وضع مستويات معيارية للجوانب المعرفية في رياضة المصارعة لطلاب كلية التربية الرياضية بجامعة بابل - عابد، محيي الدين السعيد يسن; عبد، أمير غالب حسن; قنديل، السيد المحمدي; عبدالحميد، هشام حجازي عبدالحميد (جامعة المنصورة - كلية التربية الرياضية, 2015)
• Constructing a knowledge test in the sport of wrestling-mail to students of the Faculty of Physical Education at the University of Babylon. • Developing the standard levels for use in determining the level of knowledge in the sport of wrestling to students of the Sports College of Education at the University of Babylon. Choose a random sample of 60 students in the Faculty of Physical Education at the University of Babylon, Included test axes (wrestling history, international law, physical preparation, preparation skills), electronic Cognitive test was applied is finalized and includes 43 items on the basic sample consisting of 45 students In the period between (4/3/2015-8/3/2015), The researcher used the descriptive approach. The most important findings of the researcher are Designing an electronic knowledge test in the sport of wrestling to students sporting the College of Education at the University of Babylon, Putting standard levels in the collection of knowledge to determine the level of knowledge in the sport of wrestling for the students of the Faculty of sport Education at the University of Babylon. The most important recommendations are Using the designed electronic cognitive test in the sport of wrestling periodically to evaluate the colleges of physical education students as well as the use of standard levels for electronic cognitive test in the sport of wrestling to get to know the collection of knowledge level of students of the faculties of Physical Education.
• بناء اختبار معرفي إلكتروني في رياضة المصارعة لطلاب كلية التربية الرياضية بجامعة بابل. • وضع مستويات معيارية للاستفادة منها في تحديد مستوى المعرفة في رياضة المصارعة لدى طلاب كلية التربية الرياضية بجامعة بابل. وقد اختيرت العينة بالطريقة العشوائية وكان قوامها (60) طالب من كلية التربية الرياضية بجامعة بابل، وشملت محاور الاختبار (تاريخ المصارعة، القانون الدولي للمصارعة، الإعداد البدني، الإعداد المهاري)، وتم تطبيق الاختبار المعرفي الإلكتروني في صورته النهائية من خلال الدراسة الأساسية على عينة قوامها (45) طالب وذلك في الفترة (4/3/2015- 8/3/2015) وأستخدم الباحث المنهج الوصفي. ومن أهم النتائج التي توصل إليها الباحث هي تصميم اختبار معرفي إلكتروني في رياضة المصارعة لطلاب كلية التربية الرياضية بجامعة بابل، تم وضع مستويات معيارية في التحصيل المعرفي لتحديد مستوي المعرفة في رياضة المصارعة لطلاب كلية التربية الرياضية بجامعة بابل وفقا للأسس العلمية لبناء الاختبارات المعرفية، وتم وضع مستويات معيارية للاختبار المعرفي يمكن من خلالها التعرف على مستوي طلاب تخصص رياضة المصارعة. استخدام الاختبار المعرفي الإلكتروني المصمم في رياضة المصارعة بصورة دورية لتقويم طلاب كليات التربية الرياضية إلى جانب التقويم بالملاحظة الذاتية المتبع ليكمل كل منهما الآخر، وكذلك استخدام المستويات المعيارية للاختبار المعرفي الإلكتروني في رياضة المصارعة للتعرف على مستوي التحصيل المعرفي لدي طلاب كليات التربية الرياضية.
Keywords: رياضة المصارعة -- الإختبارات المعرفية -- طلاب التربية الرياضية -- جامعة بابل ، العراق